Boron-doped, carbon-coated SnO2/graphene nanosheets for enhanced lithium storage - Liu, Yuxin; Liu, Ping; Wu, Dongqing; Huang, Yanshan; Tang, Yanping; Su, Yuezeng; Zhang, Fan; Feng, Xinliang (Chemistry - A European Journal, 2015)
Heteroatom doping is an effective method to adjust the electrochemical behavior of carbonaceous materials. In this work, boron-doped, carbon-coated SnO2/graphene hybrids (BCTGs) were fabricated by hydrothermal carbonization of sucrose in the presence of SnO2/graphene nanosheets and phenylboronic acid or boric acid as dopant source and subsequent thermal treatment. Owing to their unique 2D core-shell architecture and B-doped carbon shells, BCTGs have enhanced conductivity and extra active sites for lithium storage. With phenylboronic acid as B source, the resulting hybrid shows outstanding electrochemical performance as the anode in lithium-ion batteries with a highly stable capacity of 1165 mAhg-1 at 0.1 Ag-1 after 360 cycles and an excellent rate capability of 600 mAhg-1 at 3.2 Ag-1, and thus outperforms most of the previously reported SnO2-based anode materials. Doping for better anodes: Boron-doped carbon-coated SnO2/graphene hybrids (BCTGs) were fabricated by hydrothermal carbonization of sucrose in the presence of SnO2/graphene (TG) nanosheets and phenylboronic acid or boric acid as dopant source to give BSTGs and subsequent thermal treatment (see figure; GO: graphene oxide). Owing to the dopant B atoms in the hybrid and its 2D core-shell architecture, the hybrid obtained with phenylboronic acid as B source exhibits outstanding cycle stability after 360 cycles and an excellent rate capability at high current density.
CRIS-Team Scopus Importer:2023-03-20
Keywords: boron; doping; graphene; lithium-ion batteries; nanostructures